Catastrophic risk analysis and management for Public-Private Partnership (PPP) infrastructure systems - Qian, Qiyu (2012)
Globally, there is an increasing trend in adopting a Public-private partnership (PPP) scheme to develop large-scale infrastructure. However, little efforts are made to assess the impact of catastrophic risk on the economics (i.e. cash flows) of PPP infrastructure projects. Therefore, this study on catastrophe model for PPP infrastructure projects was undertaken with the aim to bridge the gap, what’s more important, catastrophic risk management strategy is developed for concessionaire and government respectively based on the results from catastrophe model.